Dal ricordo al racconto Il «diario» del marinaio Giulio Bogino (1943-1948): storia di un internato militare in Germania e del suo ritorno in Italia - Moscadelli, Stefano (Quaderni del Dipartimento di Scienze storiche e dei beni culturali, 2023)
The phenomenon of military internment in Germany provides a thought-provoking context that attracts various disciplinary interests. Within this volume, the author employs a primarily archival approach, interweaving historical and anthropological perspectives. The aim is to analyze and present a complex source that defies conventional categorization. The «diary» of sailor Giulio Bogino (1923-2013) - an evolving work in progress continuously revised until the early 2000s - can indeed be considered as the testimony of an internment survivor in a concentration camp in the hinterland of Hamburg, who reinterprets the memories of his captivity throughout his lifetime, ultimately transmuting them into a sort of 'popular narrative' imbued with occasional epic undertones. This volume offers a comprehensive introduction to the source itself, highlighting its distinctive features. The diary (1943-1948) is meticulously edited and presented alongside an extensive apparatus of explanatory footnotes, accompanying documents, as well as a rich collection of photographs and cartographic materials.